Effect of Psychotropic Medication on Foster Care Experience and Outcomes: A Causal Analysis using Administrative Data - Gwaltney, Angela You (International Journal of Population Data Science, 2018)
Children in foster care experienced abuse, neglect, or dependency, and for the safety and well-being of the child, must be taken out of their biological home. Not surprisingly, children in foster care have higher rates of serious emotional and behavioral problems. Although pharmacological treatments can be an important component of the treatment plan, there seems to be a higher rate of use than would be expected. An estimated 13-25% of foster children are prescribed mind- and mood-altering medication vs. 4% in the general population. Children in foster care are considered a vulnerable population and research involving these children justifiably requires additional measures to ensure their protection. As a result, studies on the use of psychotropic medication among youth in foster care have relied primarily on secondary data‚ typically administrative data. This study used linked administrative datasets to rigorously examine the effect of psychotropic medication on foster care experiences and outcomes among children who entered foster care in North Carolina between March 2006 and June 2012. The dataset was constructed by linking the North Carolina’s child welfare administrative records (also known as the Services Information System [SIS]) with the Medicaid claims database (also known as the Eligibility Information System [EIS]) for medical and mental health services received by the foster youth. Inverse probability of treatment weighting was calculated and applied to mimic a randomized study. Results revealed that children on medication stayed in care longer, less likely to experience placement disruption, and more likely to exit to adoption.